2020
DOI: 10.3390/ijerph17041185
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Endogenous and Exogenous Hormone Exposures and Breast Development in a Migrant Study of Bangladeshi and British Girls

Abstract: Timing of breast development (or thelarche) and its endogenous and exogenous determinants may underlie global variation in breast cancer incidence. The study objectives were to characterize endogenous estrogen levels and bisphenol A (BPA) exposure using a migrant study of adolescent girls and test whether concentrations explained differences in thelarche by birthplace and growth environment. Estrogen metabolites (EM) and BPA-glucuronide (BPA-G) were quantified in urine spot samples using liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In a study with Bangladeshi, firstand second-generation Bangladeshi migrants to the UK, and white British girls, the average urinary BPAG increases and is significantly higher among white British (0.007 ng/mL) and second-generation British-Bangladeshi girls (0.009 ng/mL) compared to Bangladeshi girls (0.002 ng/mL). These findings point to birthplace and growth environment as variables affecting exposure to bisphenols (84). A study within the Early Life Exposure in Mexico to Environmental Toxicants (ELEMENT) birth cohort (n = 120 girls, age 8-13 years), shows that BPA in the second trimester associates in offspring girls with higher peripubertal testosterone and higher odds of having a Tanner Stage >1 for breast development (OR/IQR: 2.2; 95%CI: 1.0, 4.5).…”
Section: Human Environmental Exposuresmentioning
confidence: 83%
“…In a study with Bangladeshi, firstand second-generation Bangladeshi migrants to the UK, and white British girls, the average urinary BPAG increases and is significantly higher among white British (0.007 ng/mL) and second-generation British-Bangladeshi girls (0.009 ng/mL) compared to Bangladeshi girls (0.002 ng/mL). These findings point to birthplace and growth environment as variables affecting exposure to bisphenols (84). A study within the Early Life Exposure in Mexico to Environmental Toxicants (ELEMENT) birth cohort (n = 120 girls, age 8-13 years), shows that BPA in the second trimester associates in offspring girls with higher peripubertal testosterone and higher odds of having a Tanner Stage >1 for breast development (OR/IQR: 2.2; 95%CI: 1.0, 4.5).…”
Section: Human Environmental Exposuresmentioning
confidence: 83%
“…We sampled first-and second-generation British-Bangladeshi women representing participants in our numerous previous studies from which we have reported rich quantitative and qualitative data on diet, lifestyles, migration, and demographic histories [10,12,13,28,29,109]. The samples analyzed here were from women aged 21-35 years, recruited in London through community contacts using snowballing techniques.…”
Section: Human Methylation Analysismentioning
confidence: 99%
“…Given the inherent problems of reproductive tissue inaccessibility in healthy human subjects, we set out to identify genes associated with altered DNA methylation in buccal tissue of Bangladeshi migrant women who had grown up in Bangladesh or the UK and to compare and integrate these findings with changes in gene expression in the reproductive tissues of a suitable mouse model. We first established such a mouse model based on findings that the "Bangladeshi childhood" reproductive phenotype, including delayed menarche and reduced ovarian reserve, was associated with increased inflammatory burden from infectious and parasitic diseases prior to puberty [10,12,13] and did not appear to be due to differential exposure to endocrine disruptors [28,29].…”
Section: Introductionmentioning
confidence: 99%